Relações entre atividade física, sintomatologia depressiva e autopercepção do envelhecimento em idosas socialmente ativas do município de Porto Alegre/RS - Casarotto, Veronica Jocasta (2017)
Aging is defined as a dynamic and progressive process, characterized by physiological, biochemical, psychological and others. This research aims to analyze the relationship between physical activity, the depressive symptoms and the ageing self-perception in elderly women socially active in Porto Alegre City/RS. This is a cross-sectional study. The instruments used were: General Survey (HQ), Geriatric Depression Scale (GDS), Self-perception of aging questionnaire (APQ) and international physical activity Questionnaire (IPAQ). The study had approval of the Scientific Committee and the Research Ethics Committee of the Institute of Geriatrics and Gerontology of PUCRS (CAAE: CEP 52097115.8.0000.5336-PUC-RS), and all the participants signed an informed consent. The statistical analyses used average, standard deviation, median, Kolmogorov-Smirnov test, analysis of variance (ANOVA), Tukey test, Kruskal-Wallis test, Pearson's Chi-square test and Spearman correlation. The significance level adopted was 5% (p < 0.05), and the analyses were performed in the version 21.0 of SPSS program. The results present a sample composed of 167 elderly women, at an average age of 70.0 (± 7.3), being the minimum age 60 and maximum 95. The age groups were divided into three groups, with the 60 to 69 year- old Group of (n = 91 54.5%), followed by the 70 to 79 year- old Group of (n = 54 32.3%) and the last group at the age of 80 or older (n = 22 13.2%). Regarding the schooling level, the incomplete elementary prevailed with 34.7% (n = 58), and complete high school with 31.7% (n = 53). On the civil status, the majority (68.3% n = 114) were declared as divorced, single or widowed. The four most prevalent diseases in the sample were, respectively, hypertension (68.9% n = 115), diabetes mellitus (17.4%, n = 29), osteoporosis (16.2% n = 27) and Dyslipidemia (15.6%, n = 26). The APQ, the positive control and positive consequence subscales presented the highest averages in the whole sample. On the scale of depression, 22.2% (n = 37) of the elderly women showed depressive symptomatology. However, this prevalence had no relationship with the age group (p = 0.693). The IPAQ questionnaire, the domain which has the greatest number of elderly women practicing more than 150 minutes a week, is the household chores (85.6% n = 143). Significant inverse associations were the physical activity practice on issues related to the work of the IPAQ with the scores of negative consequences and negative control of APQ; another relationship of physical activity with the means of transport of the IPAQ, with scores of negative control of the APQ and scores of depressive symptoms of GDS; and the association of physical activity in leisure-related issues with the scores of negative consequence of the APQ and depressive symptoms of the GDS.